Ethnonyms from the Southern Region of Peru (working hypothesis) - Ballón Aguirre, Enrique (2013)
One of the lexical areas not explored systematically is that of the ethnonyms of Andean Spanish. This article intends to examine, through a lexicological hypothesis, the semantic conformation of those ethnonyms, and demonstrate, by way of example, the presence of diglossic syntagmas (expressions, nicknames, proverbs) in the colloquial speech of the southern communities of this country.